Drought resistance testing of several local rice genotypes based on morphological and molecular markers - LAILA NAZIRAH; JAMILAH JAMILAH; HALIM AKBAR (Society for Indonesian Biodiversity, 2025)
Abstract. Nazirah L, Jamilah, Akbar H. 2025. Drought resistance testing of several local rice genotypes based on morphological and molecular markers. Biodiversitas 26: 1202-1210. Drought is a major challenge in rice cultivation, leading to reduced productivity. Therefore, it is essential to develop drought-resistant rice varieties. This study aimed to assess rice genotypes' morphological and molecular characteristics to identify potential parental lines with drought-resistant traits. The experiment was conducted across two seasons under optimal and minimal watering, arranged in a Randomized Complete Block Design (RCBD) with three replications. Seven genotypes were evaluated (i) Unsyiah Cakep (UC77); (ii) Unsyiah Seumeulu (US20); (iii) Cot Bada (CBD08, CBD04); (iv) Sigunca (SG02); (v) Sigupai (UA12); and (vi) Rajasa. Molecular analysis utilized SSR markers RM38, RM6130, and RM5423. The results revealed a significant genotype-by-environment interaction (p<0.01) for yield traits. Optimal watering enhanced productivity compared to minimal watering in both seasons. Productivity correlated positively with the number of productive tillers, panicle length, and filled grains in both environments. Under optimal watering, it was also correlated with 1000-grain weight, whereas under minimal watering, it correlated with total grain number. Heritability values ranged from moderate to high. MGIDI-based selection identified UC77, SG02, and UA12 as promising genotypes. GGE biplot analysis indicated UC77 was best suited for the rainy season, while SG02, UA12, and CBD08 performed well under minimal watering in the dry season. Based on molecular analysis, RM38 and RM6130 were highly informative for distinguishing between the tested genotypes. A dendrogram presented genotypes UA12 and UC77which exhibited the lowest genetic similarity, showing potential for breeding high-yielding and drought-tolerant rice varieties.